Preliminary Genetic Manipulation Studies On Muskmelon (Cucumis Melo L.) Using Protoplast Technology - Tan, Siang Hee (1994)

(untitled)
In this study, parallel attempts have been made to initiate somatic embryos from two different explants on various hormone combinations and the results obtained were then applied to establish plant regeneration system for protoplastderived macrocalli. Simultaneously, optimisation of plant transformation system using electroporation techniques (direct uptake) were carried out to facilitate future research on the genetic improvement of muskmelon.Somatic embryos were successfully initiated from Birdie radicle region and Hami melon cotyledon using MS medium containing 1.0 mg/L 2,4-0, 2.0 mg/L NAA and 0.1 mg/L BAP and medium gave 2.0 mg/L NAA and 0. 1 mg/L BAP, respectively. The somatic embryos developed into normal plantlets after subculturing onto hormone-free M S media solidified with 0.4% (w/v) Gelrite®.Both Birdie and Hami melon protoplasts were successfully isolated using cotyledons of seven day in vitro seedlings incubated in different enzyme concentrations. Birdie melon explants were incubated in 0.05% (w/v) pectolyase Y23 and 1.0% (w/v) cellulase RS while Hami melon explants were incubated in 0.025% (w/v) Pectolyase Y23 and 1 .0% (w/v) Cellulase RS for 1.5 hours . . Subsequently, Birdie protoplast which were cultured onto semi-solid (0.09% Gelrite®) medium containing 1/2 strength MS supplemented with 0.1 mg/L NAA and 0.5 mg/L BAP gave the highest number of macrocolonies formation (60.96 number of colonies/field) after 30 days in culture, while Hami melon protoplast gave highest number of macrocolonies formation (30.48 number of colonies/field) in liquid culture containing 1/2 strength MS supplemented with 0.5 mg/L NAA and 1 .0 mg/L zeatin. Further experiments were conducted to establish the regeneration system for the macrocalli with addition of auxin and cytokinin, sucrose, growth regulators and amino acids. The results obtained showed that the macrocalli had potential to regenerate into plantlets on two types of medium (0.5 mg/L and 2.0 mg/L BAP). However. further studies must be performed to obtain a more suitable regeneration media from protoplast-derived macrocalli.In this study, genetic transformation of muskmelon protoplasts were carried out using electroporation system. Using pBI22 1 as a standard, various parameters for electroporation were optimised and the GUS activities were assayed. Pulse strength of 3.0 kV/cm, single pulse, 10.0 us pulse length, 25.0 ug/ml plasmid DNA and 15 hours incubation time were optimum for efficient DNA uptake and transient assay. Treatment of the protoplast with external stimulus such as UV irradiation in the presence of different plasmid constructs showed that the plasmid pYCN01 and pYCN02 containing different length of PSPAL promoter fragment gave higher GUS activity compared to the CaMV 35S promoter. The results indicate that ultra violet irradiation of the protoplasts was at least partly responsible for the activation of PAL promoter.